Harvesting vortex energy in the cylinder wake with a pivoting vane. (August 2015) - Li, Saiwei; Sun, Zhiqiang
Abstract: The feasibility of harvesting energy from a steady flow at Reynolds number Re  = 100 is studied numerically. A bluff body placed in the flow induces a stable vortex street in its wake, where a vane harvester is placed and directed parallel to the flow. The vane is pivoted at its leading edge, while the rest is unconstrained. We find that the periodic pressure difference between the two sides of the vane is sufficient to force the vane harvester into a steady swing, whose mechanical energy may be used to generate small amounts of electricity. An optimization process of the vane harvester is then conducted. Three parameters are varied independently for investigation, the gap between the vane and the bluff body, the length of the vane, and the mass of the vane. It is found that the energy harvesting performance is strongly related to two vortex mechanisms that drive the vane motion: local vortex dissipation along the vane and pressure gradients induced by large vortices in the wake. Also, constructive or destructive interaction of the vortices at the vane tip also plays an important role in vane motion and its energy harvesting ability. Highlights: We apply a pivoting vane to harvest energy of the shedding vortices from a cylinder. The cylinder-vane gap, vane length and vane mass are varied for optimal performance. Different vane motion patterns are observed for varying vane parameters. The merits of the different vane motion patterns are analyzed and discussed.